THE ROLE OF E-MARKETING IN GENERATING CONSUMER BUYING INTEREST IN SINAR BAHARI BANDUNG FISH MEATBALLS - Sutopo, Sutopo; Sudianto, Sudianto; Hamid, Abdul (Journal of Management and Innovation Entrepreneurship (JMIE), 2024)
The role of E-Marketing in generating consumer buying interest in the Sinar Bahari Bandung Fish Meatballs is as a tool for communicating, promoting, and selling products via the Internet. E-Marketing refers to the application of marketing principles and techniques through electronic media, more specifically the Internet. By using E-Marketing, companies can increase consumer buying interest by offering product information that contains quality, features, and satisfactory service. This can be done through various strategies, such as developing interesting content, promotions via social media, and providing special discounts or promos. E-Marketing can also use data analysis tools to understand consumer needs and purchasing interests so that they can adapt the products or services provided. The role of e-marketing in generating consumer buying interest in the Sinar Bahari Bandung Fish Meatballs is very important. In online marketing strategies, e-marketing is used to increase consumer buying interest, both in online and offline purchases. E-marketing has several elements that can influence consumer buying interest, such as promotions, namely e-marketing can use short-term incentives such as discounts, promotions, and offers to encourage purchases or sales. Price, namely E-marketing can offer affordable and appropriate prices so that consumers can choose products that suit their budget. Product Quality, namely E-marketing can offer products that are high quality and follow consumer desires. Content and Design, namely E-marketing, can use attractive and stunning content and design so that consumers are more interested in buying. Online Orders, namely E-marketing, can simplify the online order process so that consumers can order products easily and quickly. Customer Service: E-marketing can offer good customer service, such as fast and easy shipping, returns, and replacement of goods. In the case of Sinar Bahari Bandung Fish Meatballs, e-marketing can be used to promote products, offer discounts, and simplify the online ordering process.